2001
DOI: 10.1080/028418601750071091
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Inguinal and Radical Ilioinguinal Lymph Node Dissection in Patients with Palpable Melanoma Metastases to the Groin - An Analysis of Survival and Local Recurrence

Abstract: The present study addresses the question whether an extended ilioinguinal dissection as compared to an only superficial inguinal dissection improves survival and/or local tumour control after the appearance of palpable melanoma metastases to the groin. We retrospectively analysed the data of 104 patients with 69 ilioinguinal and 35 superficial inguinal dissections (median follow up 127 months). Prognostic factors of survival and groin recurrence were assessed using Kaplan-Meier estimation and Cox proportional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 19 publications
3
15
0
2
Order By: Relevance
“…6,12,13,20 (Table 4) Like other published studies, we found that number of positive nodes and extracapsular extension are better predictors of poor outcome than palpable tumor burden in the groin. 20–22 Thus, even in patients with palpable disease, SGD is appropriate for clearance of lymph nodes from the groin. The obvious caveat to this is that patients must be evaluated preoperatively and have no evidence of iliac metastases prior to SGD.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…6,12,13,20 (Table 4) Like other published studies, we found that number of positive nodes and extracapsular extension are better predictors of poor outcome than palpable tumor burden in the groin. 20–22 Thus, even in patients with palpable disease, SGD is appropriate for clearance of lymph nodes from the groin. The obvious caveat to this is that patients must be evaluated preoperatively and have no evidence of iliac metastases prior to SGD.…”
Section: Discussionsupporting
confidence: 82%
“…However, overall recurrence rate was 33.6%, and the fact that the study evaluated palpable disease may factor into that rate. 20 The current study included patients with palpable disease and did not see as high a rate of local recurrence after SGD. Perhaps our use of preoperative evaluation to exclude patients with iliac disease produced a patient population with lower overall regional disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…Even comparison of patients with superficial involved nodes only showed no difference, indicating that the extent of groin surgery does not influence outcome (data not shown; p  = 0.217). Also in other studies, it has been demonstrated that extent of groin surgery, regardless of presence or absence of deep lymph node involvement in CGD patients, has no effect on survival 8,10,16…”
Section: Discussionmentioning
confidence: 87%
“…Also 5-year DFS rates were virtually identical, i.e., 18% for CGD and 16% for SGD. Patients with CGD with positive deep nodes have the poorest prognosis, with OS ranging from 6% to 34% in the literature 7,8,10,14–16. (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Well-established standard surgical techniques of TLND were considered as standard of care (modified neck dissection, axillary dissection including nodal levels I–III with preservation of the pectoralis minor muscle, ilioinguinal dissection). Our surgical approaches of TLND have been previously described 8,9. An abdominoperineal rectum extirpation along with the enlarged paraproctic node metastases was performed on one patient.…”
Section: Methodsmentioning
confidence: 99%